Powszechność funkcji keryksa w Kościele starożytnym. Stanowisko Klemensa Aleksandryjskiego - Drączkowski, Franciszek (Vox Patrum, 2003)
The term to kerygma in Ciemens of Alexandria’s writings means both an action performed in time and the contents, substance, subject of the Good News the contents of the Gospel. The conveyor of the kerygmat is a word, which can be said or written. On the basis of this assumption Clemens talks about two kinds of kerygma: oral and written. In the times of persecution the written transmission accomplished the principle of kerygmat universality in a fuller way, as it reached ail environments, also the circles that were unfavorable or hostile towards Christianity.